2016
DOI: 10.21315/jcdc2016.21.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Studying the Reasons for Delay and Cost Overrun in Construction Projects: The Case of Iran

Abstract: 2016). Studying the reasons for delay and cost overrun in construction projects: The case of Iran.Abstract: Undesirable delays in construction projects impose excessive costs and precipitate exacerbated durations. Investigating Iran, a developing Middle Eastern country, this paper focuses on the reasons for construction project delays. We conducted several interviews with owners, contractors, consultants, industry experts and regulatory bodies to accurately ascertain specific delay factors. Based on the result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 48 publications
(43 reference statements)
0
55
0
3
Order By: Relevance
“…Unique factors (with the frequency of three or less) are: "'Slow decision making process by owner" in Norway [90], UAE [84], and Oman [98]; "Changes in material types and specifications during construction" in Saudi Arabia [102], Turkey [117], and Zambia [113]; "Change/selection of subcontractors in the project" in India [79], Saudi Arabia [112], and Vietnam [105]; "Mobilization delay" in India [127], Malaysia [109], and Malawi [81]; "Site constraints (site blockage, impact of other's land)" in Bangladesh [87], Cambodia [103], and countries with high geopolitical risks [104]; "Impact of subsurface (underground) conditions" in Libya [91], Cambodia [103], and Egypt [123]; "Conflict between parties' in Iran [101], Turkey [70], and Egypt [107]; "Errors in construction" in Iran [93], Zambia [113], and Denmark [89]; "Fluctuation in price of materials" in Saudi Arabia [102] and Ghana [100]; "Conflict between labours" in Saudi Arabia [88] and Zambia [113]; "Labour strikes" in countries with high geopolitical risks [104] and Zambia [113]; "Using inappropriate construction methods" in India [92] and Iran [110]; "Insufficient/inaccurate document preparation" in Turkey [70] and Iran [110]; "Inaccurate first drafts/plan" in Iran [110] and Taiwan [132]; "Delay/weak interaction due to vendor" in India [127] and Oman…”
Section: Key Factors Identified In the Delay Literaturementioning
confidence: 99%
“…Unique factors (with the frequency of three or less) are: "'Slow decision making process by owner" in Norway [90], UAE [84], and Oman [98]; "Changes in material types and specifications during construction" in Saudi Arabia [102], Turkey [117], and Zambia [113]; "Change/selection of subcontractors in the project" in India [79], Saudi Arabia [112], and Vietnam [105]; "Mobilization delay" in India [127], Malaysia [109], and Malawi [81]; "Site constraints (site blockage, impact of other's land)" in Bangladesh [87], Cambodia [103], and countries with high geopolitical risks [104]; "Impact of subsurface (underground) conditions" in Libya [91], Cambodia [103], and Egypt [123]; "Conflict between parties' in Iran [101], Turkey [70], and Egypt [107]; "Errors in construction" in Iran [93], Zambia [113], and Denmark [89]; "Fluctuation in price of materials" in Saudi Arabia [102] and Ghana [100]; "Conflict between labours" in Saudi Arabia [88] and Zambia [113]; "Labour strikes" in countries with high geopolitical risks [104] and Zambia [113]; "Using inappropriate construction methods" in India [92] and Iran [110]; "Insufficient/inaccurate document preparation" in Turkey [70] and Iran [110]; "Inaccurate first drafts/plan" in Iran [110] and Taiwan [132]; "Delay/weak interaction due to vendor" in India [127] and Oman…”
Section: Key Factors Identified In the Delay Literaturementioning
confidence: 99%
“…In this category, materials and equipment are considered under resources. The factors in this group are lack of skilled workers [31,53,67], unskilled operator/technical person [4,35,45], escalation of resources price [53,72,73], equipment failure [13,16,67], shortage of equipment [17,21,33], delay in material procurement [14,27,69], slow delivery of material and equipment [12,17,49], and transportation problem [6,31,74]. In general, the factors lack of skilled workers, delay in material procurement and delivery, and shortage of equipment are most frequent in developing countries.…”
Section: Ementioning
confidence: 99%
“…Some project related problem such as inaccurate site investigation [12,13], site constraints [21,77], change in site condition [24,78,87] obsolete construction methods and technologies [24,53,79], and delay in site clearance [23,81,82] were identified as the potential causes of construction delay. In this group most of the factors are moderately important regardless of geographic boundaries.…”
Section: Fmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these factors are some not previously highlighted in other studies in Malaysia. [11] presented a statistical model of factors contributing to delays in the construction industry, classified into four categories related respectively to owners, consultants, law and regulations, and general defects. They concluded that the most important and significant factors among these were budgeting and resource allocation defects.…”
Section: Literature Reviewmentioning
confidence: 99%